A Narrative Review of the Conventional and Contemporary Components of an Aesthetically Pleasing Smile - Sapna Rani; Pankaj Dhawan; Roshni Lekhi; Simran Chadha (Journal of Clinical and Diagnostic Research, 2024)
The personality of a person is reflected by smile of that person. Smile designing encompasses hard tissue and soft-tissue components. The treatment plan includes facial, dental and gingival analysis to execute analysis and formulate treatment plan. The main objective of smile designing is to meet patient expectations and enhance patient’s smile with improved quality. Now, smile designing has shifted to digital platform. There has been evolution in smile designing from 2-dimensional (2D) to 3-dimensional (3D) and now further to 4-dimensional (4D). The techniques include veneers and laminates, bonded restorations, modification on tooth form and various prosthetic procedures including Digital Smile Designing (DSD). The artificial intelligence can be applied only when parameters, components and various principles are known to the clinician. Smile designing comprises of aesthetic and cosmetic principles for reconstruction of smile. Certain reference lines are to be considered for designing of aesthetic appealing smile. The present narrative review emphasises on all the factors which should be considered in smile designing and also the new concepts for smile designing.